Answer:
[tex]\Large \boxed{k=2x + \frac{-7}{3}} \\ \\ \\ \Large \boxed{x=\frac{1}{2} k+\frac{7}{6}}[/tex]
Step-by-step explanation:
Solving for k:
[tex]\sf 3k+16=9+6x[/tex]
Subtracting 16 from both sides.
[tex]\sf 3k=6x-7[/tex]
Dividing both sides by 3.
[tex]\displaystyle \sf k=2x + \frac{-7}{3}[/tex]
Solving for x:
Flipping the original equation.
[tex]\sf 6x+9=3k+16[/tex]
Subtracting 9 from both sides.
[tex]\sf 6x=3k+7[/tex]
Dividing both sides by 6.
[tex]\sf \displaystyle x=\frac{1}{2} k+\frac{7}{6}[/tex]